Implementation of Eucharistic Liturgical Gestures at Saint Christopher Parish, Siborongborong - Jenius Frans Bonar Gultom; Paulinus Tibo (International Journal of Christian Education and Philosophical Inquiry, 2026)
This study aims to describe and analyze the understanding of the faithful and the implementation of Eucharistic liturgical gestures at Saint Christopher Parish, Siborongborong. Liturgical gestures such as the sign of the cross, standing, sitting, kneeling, and striking the chest are essential elements of active participation in the Eucharistic celebration. These gestures are not just physical actions but carry profound spiritual significance. This research employed a descriptive qualitative approach, with data collected through participant observation, in-depth interviews, and documentation. The findings reveal that the faithful’s understanding of the symbolic meaning of these gestures remains limited, which leads to a tendency to perform them mechanically without deep spiritual reflection. This lack of understanding results in a disconnect between the physical actions and their intended spiritual effects. Nevertheless, in practice, the faithful generally follow these gestures in accordance with the liturgical norms of the Church. Therefore, the study emphasizes the need for continuous and contextual liturgical formation programs. These programs should aim to deepen the awareness and spiritual engagement of the faithful in the Eucharistic celebration, ensuring that the gestures are not just performed but fully understood and internalized.